The five George Masons : patriots and planters of Virginia and Maryland - Copeland, Pamela C. (Pamela Cunningham), 1906-2001 (Published for the Board of Regents of Gunston Hall by the University Press of Virginia, 1975)
"This book is the outgrowth of research efforts to help the Board of Regents of Gunston Hall appropriately furnish the home of George Mason and better interpret its history through a greater knowledge of Mason's personal life, business enterprises, and political activities."--Preface